Distinct expression of interleukin (IL)-36α, β and γ, their antagonist IL-36Ra and IL-38 in psoriasis, rheumatoid arthritis and Crohn's disease. (22nd February 2016) - Boutet, M-A; Bart, G; Penhoat, M; Amiaud, J; Brulin, B; Charrier, C; Morel, F; Lecron, J-C; Rolli-Derkinderen, M; Bourreille, A; Vigne, S; Gabay, C; et al.
Summary: Interleukin (IL)-36α, IL-36β and IL-36γ are expressed highly in skin and are involved in the pathogenesis of psoriasis, while the antagonists IL-36Ra or IL-38, another potential IL-36 inhibitor, limit uncontrolled inflammation. The expression and role of IL-36 cytokines in rheumatoid arthritis (RA) and Crohn's disease (CD) is currently debated. Here, we observed that during imiquimod-induced mouse skin inflammation and in human psoriasis, expression of IL-36α, γ and IL-36Ra, but not IL-36β and IL-38 mRNA, was induced and correlated with IL-1β and T helper type 17 (Th17) cytokines (IL-17A, IL-22, IL-23, CCL20). In mice with collagen-induced arthritis and in the synovium of patients with RA, IL-36α, β, γ, IL-36Ra and IL-38 were all elevated and correlated with IL-1β, CCL3, CCL4 and macrophage colony-stimulating factor (M-CSF), but not with Th17 cytokines. In the colon of mice with dextran sulphate sodium-induced colitis and in patients with CD, only IL-36α, γ and IL-38 were induced at relatively low levels and correlated with IL-1β and IL-17A. We suggest that only a minor subgroup of patients with RA (17–29%) or CD (25%) had an elevated IL-36 agonists/antagonists ratio, versus 93% of patients with psoriasis. By immunohistochemistry, IL-36 cytokines were produced by various cell types in skin, synovium and colonic mucosa such as keratinocytes, CD68 + macrophages, dendritic/Langerhans cells and CD79α + plasma cells. In primary cultures of monocytes or inflammatory macrophages (M1), IL-36β and IL-36Ra were produced constitutively, but IL-36α, γ and IL-38 were produced after lipopolysaccharide stimulation. These distinct expression profiles may help to explain why only subgroups of RA and CD patients have a potentially elevated IL-36 agonists/antagonists ratio.